2013
DOI: 10.1128/jvi.01642-13
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of Virus Infection but Not Catalytic dNTPase Activity Is Regulated by Phosphorylation of SAMHD1

Abstract: bSAMHD1 is a host protein responsible, at least in part, for the inefficient infection of dendritic, myeloid, and resting T cells by HIV-1. Interestingly, HIV-2 and SIVsm viruses are able to counteract SAMHD1 by targeting it for proteasomal degradation using their Vpx proteins. It has been proposed that SAMHD1 is a dGTP-dependent deoxynucleoside triphosphohydrolase (dNTPase) that restricts HIV-1 by reducing cellular dNTP levels to below that required for reverse transcription. However, nothing is known about S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
197
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(217 citation statements)
references
References 36 publications
15
197
1
Order By: Relevance
“…The in vivo and in vitro studies reported here with recombinant SAMHD1 proteins reveal that the T592D phosphomimetic variant is an active dNTPase, consistent with previous reports (30,39). It is evident, however, that the T592D substitution weakens the in vitro dNTPase activity of the recombinant enzyme as well as its ability to lower cellular dNTP levels.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The in vivo and in vitro studies reported here with recombinant SAMHD1 proteins reveal that the T592D phosphomimetic variant is an active dNTPase, consistent with previous reports (30,39). It is evident, however, that the T592D substitution weakens the in vitro dNTPase activity of the recombinant enzyme as well as its ability to lower cellular dNTP levels.…”
Section: Discussionsupporting
confidence: 77%
“…Associates with SAMHD1 C-terminal Domain-SAMHD1 antiviral function was reported to be modulated by mutations in the C-terminal region, including a phosphomimetic substitution for Thr-592 (25,29,30,39). This threonine was shown to be a substrate for CDK1 and/or CDK2 kinase in complex with S phase cyclinA2 (13,29).…”
Section: Cyclina2mentioning
confidence: 99%
“…SAMHD1 is phosphorylated at different sites, but only pT592 was found to be related to the state of cellular growth, being present only in proliferating cultures [15,21]. Previous work by Yan et al showed that pT592 is present in S and G2/M in subpopulations of leukocytes isolated by cell sorting [18].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated T592 is believed to have a regulatory function but how it relates to SAMHD1 activity and/or protein stability is still questioned. Biochemical studies with recombinant phosphomimetic (T592D/E) and non-phosphorylatable (T592A/V) SAMHD1 mutants yielded conflicting results regarding tetramer stability and enzymatic properties [15,1721]. In live cells, the effects of SAMHD1 phosphorylation were investigated by ectopic over-expression of SAMHD1 mutants and the restriction of viral infection or dNTP pool decrease, both readouts of SAMHD1 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well established that SAMHD1 does not restrict HIV-1 in dividing cells where the protein is phosphorylated at residue Thr-592 (21, 28 -32), the effect of this phosphorylation on SAMHD1 dNTPase activity is unclear. The phosphomimetic mutants of SAMHD1 (T592E/T592D) impair the ability to block HIV-1 infection in non-dividing cells, but were observed to retain the ability to hydrolyze dNTPs in vitro and reduce the cellular dNTP levels (31,33). In contrast, disruption of SAMHD1 Thr-592 phosphorylation either by a cyclin-dependent kinase 4/6 (CDK4/6) inhibitor or by SAMHD1 mutants defective for cyclin A2 interaction results in * This work was supported in part by National Institutes of Health Grants AI102778 (to Y.…”
Section: Cd4mentioning
confidence: 99%